2008
DOI: 10.1055/s-2008-1047559
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Probability and D-dimer Testing: How Should We Use Them in Clinical Practice?

Abstract: Venous thromboembolism (VTE) is extraordinarily common and is a major cause of morbidity and mortality. However, accurate and timely diagnosis of VTE is confounded by its kaleidoscopic presentation. Clinical prediction rules (CPRs) and D-dimer testing have both been increasingly employed to clarify the complex decision making required in such cases. Formal clinical pretest probability now serves as the root of algorithms for the diagnosis of DVT and PE. A low pretest probability of VTE plus a negative D dimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
0
13
0
2
Order By: Relevance
“…However, a number of previous studies demonstrated that D-dimer levels are associated with thromboembolism risk. [14][15][16][17][18]20 We are continuing to follow the patients in this study to evaluate thromboembolic events. Another limitation is the study design that means a nonrandomized design, no clinical trial, and a small number of cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, a number of previous studies demonstrated that D-dimer levels are associated with thromboembolism risk. [14][15][16][17][18]20 We are continuing to follow the patients in this study to evaluate thromboembolic events. Another limitation is the study design that means a nonrandomized design, no clinical trial, and a small number of cases.…”
Section: Discussionmentioning
confidence: 97%
“…Measurement of D-dimer levels is a gold standard for diagnosing thrombosis and identifying increased risk of thrombotic events. [15][16][17][18][19] Elevated serum Ddimer levels indicate a high risk of thrombosis. 20 Many long-term prospective studies have demonstrated an association between D-dimer and thromboembolism or coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the 3-risk group model, patients with a score of 0 or less are considered low risk patients, the score of 1-2 presents moderate risk, and the score of 3 or more is classified as high risk, with 5%, 17% and 53% probability of DVT respectively. In the more frequently used 2-risk group evaluation, patients are stratified as DVT unlikely (the Wells score < 2) or DVT likely (the Wells score ≥ 2) where probability of DVT is 6% and 28% respectively [14,15]. By combining this score with the results of a highly sensitive D-dimer assay and proximal leg vein ultrasound scan further evaluation is possible [16].…”
Section: Discussionmentioning
confidence: 99%
“…To assist with routine clinical assessment and the clinical Gestalt (i.e., unstructured estimate of the likelihood for PE), prediction rules have been developed that are able to more precisely quantify the pre-test probability of PE and help guide the diagnostic process and triaging of patients with suspected PE. Several pre-test probability scores have been studied, including the Wells and modified Wells score, 20,21 the revised Geneva score, 22 and the pulmonary embolism rule out criteria (PERC) 23 (►Tables 1-3).…”
Section: Risk Scoresmentioning
confidence: 99%